Dampak Pandemi Covid-19 Terhadap Sektor Perbankan di Indonesia - rosidi Muhammad Rosidi; Cathelya Vionna Githa (Universitas Sains dan Teknologi Komputer, 2022)
The outbreak of the COVID-19 virus in Indonesia, then it can cause a big impact on various sectors including the financial and service industries, one of them is the banking industry. The lockdown and social distancing and new normal policies carried out by the government turned out to be contrary to certain sectors that were unable to carry out these government policies efficiently, one of them is the banking sector. The purpose of this journal is to find out how big the impact of COVID-19 on the banking economic activities in Indonesia, as well as what solutions are given to overcome the impacts that arise from these problems.